Local Wisdom-Based Character Building Empowerment at Junior High Schools In Indonesia - Niken Rahmawati; Fatah Syukur; Darmu'in Darmu'in (STAI Hubbulwathan Duri, 2023)
Adolescent moral abnormalities are caused by several circumstances, including the weak grasp of religion in a culture where science can accomplish everything. Character education in schools is difficult because student character issues persist. The amount of moral crisis cases suggests that educational institutions are failing to transform student character. This study aimed to determine the implementation of character education policies in schools, the role of teachers in character education, and the role of parents in character education, character education models. This research was conducted using quantitative research using the one-group pretest-posttest design method. In the research, the sampling was carried out by means of saturated sampling. The sample of this study were 30 students of grade seven in junior high school. Based on the results of this study, the results of hypothesis testing using the non-parametric Smirnov test using SPSS 21 can be concluded that (tcount ttable) with tcount = 10.30 ttable = 2.035. Then Ha is accepted, and Ho is rejected so that it can be concluded that the application of character education based on local wisdom is an implication of character conditions that are reduced by various impacts of current scientific and technological advances. The importance of character education based on local wisdom in schools is to remind and cultivate the noble values of the Indonesian nation.